Independent National Electoral Commission and Campaign Financing Monitoring in Nigeria: The 2015 General Elections - Sule, Babayo; Mohd Sani, Mohd Azizuddin; Mat, Bakri (Penerbit Universiti Utara Malaysia, 2017)
The Independent National Electoral Commission (INEC) is the electoral umpire responsible for the conduct of general elections in Nigeria and other related electoral activities since the resurgence of democratic rule in 1999.One of these important electoral activities carried out by INEC is campaign monitoring and political party financing activities as provided in the Nigerian Constitution and the 2010 Electoral Act.This paper examined the role of INEC in monitoring candidates and parties’ expenditure during the 2015 General Elections.The major problem was the way parties and candidates violated the regulations while INEC as the monitoring body was watchful without any concrete action.The paper used the qualitative method of data collection and analysis where the researchers went to the field and consulted informants in the affected agencies and individuals through interviews and Focus Group Discussions. The data obtained from the field was analysed using tables and other techniques of qualitative data analysis.The paper concludes that, politicians and their political parties spent above the campaign spending limits as provided by law in the 2015 General Elections and the electoral body (INEC) did not monitor properly the campaign spending due to lack of political will from policy-makers and loopholes in the law that empowered them to monitor the spending. The research recommends that for proper and effective campaign financing monitoring in future elections, INEC should be mandated to monitor all politicians and their activities during and after elections, the anti-graft agency (EFCC) should be involved in screening candidates while the Code of Conduct Bureau should be reinforced in watching public servants’ assets.